L’animale narrante. Brian Boyd e l’origine delle storie - CIFUNI, SALVATORE (S&F_scienzaefilosofia.it, 2016)
The storytelling Animal. Brian Boyd and the origin of Stories This paper will discuss about Literary Darwinism, a new branch of literary criticism that tries to explain storytelling in evolutionary terms. In particular, It will deal with the thesis proposed by Bryan Boyd, the most cited author of LD, according to which narrative is the most powerful tool to share and shape attention – especially in the form of fiction, which allows human beings to go beyond the here and now. Therefore, after having described his proposal and, briefly, its weaknesses, I will focus on the most interesting part of It: the one about ontogeny. So, using Boyd as a starting point, I will study the importance of narrative for the development of our most relevant cognitive skills.